KESIAPAN MENGAJAR MAHASISWA PRODI PENDIDIKAN TEKNIK BANGUNAN FT-UNP SEBAGAI CALON GURU PROFESIONAL DI SMK - Rama Dhonal; Dr. Rijal Abdullah, MT (Universitas Negeri Padang, 2019)
Abstract—This research aims to reveal the Teaching Readiness of Students of Building Engineering Education Study Program FT-UNP as Prospective Professional Teachers in Vocational Schools. This type of research is descriptive. This research was conducted in the Civil Engineering Department of the FT-UNP. Respondents in this study were students who had implemented PPLK in the school year July-December 2017 / 2018. Data collection techniques in this study used questionnaires. While the sampling technique used is total sampling. In this study the number of respondents was 44 people. The results of this study indicate that the students of the Building Engineering Education Study Program FT-UNP are in the category both in terms of the level of readiness to teach pedagogical and professional competencies. Keywords: Readiness, Teach, Professional Teachers.